Modified porous carbon-based composite material as well as preparation method and application thereof

By infiltrating the sol of the boron-containing precursor and titanium precursor into the pores of the porous carbon material and calcining the process, a modified porous carbon-based composite material was prepared, which solved the problem of insufficient removal capacity of existing biochar adsorbents, and achieved efficient removal of heavy metal ions and organic matter in wastewater, and the process was environmentally friendly and economical.

CN119869453AActive Publication Date: 2025-04-25QUFU NORMAL UNIV
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202510121919.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-26
Publication Date
2025-04-25
Estimated Expiration
2045-01-26

AI Technical Summary

Technical Problem

The existing biochar adsorbents are not ideal in removing heavy metal ions and organic matter in industrial wastewater, and the modified activator is highly polluted to the environment.

Method used

Modified porous carbon-based composite materials were prepared by compounding the activator components and infiltrating the sol containing boron and titanium precursors into the pores of the porous carbon material, calcining treatment, doping boron elements and titanium dioxide. This material enhances the removal performance of pollutants in wastewater through the synergistic effect of adsorption and photocatalysis.

Benefits of technology

The modified porous carbon-based composite material produced has a more complex pore structure, more surface defects and richer functional groups, which significantly improves the removal performance of metal ions and organic matter in wastewater, and has a simple process, green and environmentally friendly and low cost.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119869453A_ABST
    Figure CN119869453A_ABST
Patent Text Reader

Abstract

The invention discloses a modified porous carbon-based composite material and a preparation method and application thereof in the technical field of adsorbent preparation. According to the invention, by compounding the activator component and applying the activator component to the preparation process of the porous carbon material, the porous carbon material with rich pore structures can be prepared; according to the preparation method, sol containing a boron precursor and a titanium precursor is infiltrated into pores of the porous carbon material and is calcined, so that boron and titanium dioxide are successfully doped into the pores of the porous carbon material, and modification treatment of the porous carbon material is realized; the prepared modified porous carbon-based composite material can enhance the removal performance of metal ions and organic matters in wastewater through the synergistic effect of adsorption and photocatalysis. The method has the advantages of being simple in process, environmentally friendly, low in cost and the like, and the prepared modified porous carbon-based composite material has excellent removal performance on metal ions and organic matter in wastewater and shows obvious economic value in the field of sewage treatment.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present application belongs to the technical field of adsorbent preparation, and in particular relates to a modified porous carbon-based composite material, a preparation method and an application thereof. Background Art

[0002] The chemical industry plays a vital role in modern society. However, its huge production volume also leads to the generation of a large amount of wastewater, which contains various organic matter, heavy metals and other harmful substances. These wastewaters pose a serious threat to the environment and ecosystem. In recent years, with the improvement of environmental protection awareness and the increasingly stringent environmental regulations, the research and practice of chemical industry wastewater treatment technology has become particularly important. The treatment of chemical wastewater involves complex chemical, biological and physical processes, and its characteristics include the complex diversity of wastewater components, high concentration of pollutants, and great harm to the ecological environment.

[0003] At present, adsorption treatment technology is a simple and effective technology for treating industrial wastewater. It is widely used in the treatment of industrial wastewater containing heavy metal ions, dye wastewater, petrochemical wastewater, etc. Commonly used technologies for industrial wastewater treatment include biochar adsorption, zeolite exchange, etc.

[0004] Biochar is a type of insoluble, stable, highly aromatic carbon-rich material formed by pyrolysis of biomass under oxygen-limited or anaerobic conditions. As an economical and environmentally friendly adsorbent, biochar has been widely used to remove heavy metals from water. However, traditional biochar often has some disadvantages. For example, the original biochar has a small specific surface area, a small content of surface functional groups, and a poor adsorption effect on metal ions; some modified biochar activators are highly polluting and will cause pollution to the environment. In addition, the removal effect of pollutants by simple adsorption technology may not be ideal, and sometimes more adsorption materials need to be added to achieve the ideal effect.

[0005] Therefore, providing a new modified porous carbon-based composite material to solve the above-mentioned defects is an urgent problem to be solved. Summary of the invention

[0006] In order to overcome the deficiencies of the prior art, the purpose of the present invention is to provide a modified porous carbon-based composite material, a preparation method and its application; the present invention can prepare a porous carbon material with a rich pore structure by compounding an activator component and applying it to the preparation process of the porous carbon material; at the same time, the present invention successfully doped boron and titanium dioxide into the pores of the porous carbon material by infiltrating a sol containing a boron precursor and a titanium precursor into the pores of the porous carbon material and calcining it, thereby achieving a modification of the porous carbon material, so that the prepared modified porous carbon-based composite material can enhance its removal performance of metal ions and organic matter in wastewater through the synergistic effect of adsorption and photocatalysis. The present invention has the advantages of simple process, green environmental protection, low cost, etc. At the same time, the prepared modified porous carbon-based composite material has excellent removal performance for metal ions and organic matter in wastewater, and shows obvious economic value in the field of sewage treatment.

[0007] To achieve the above object, the present invention provides the following technical solutions: A method for preparing a modified porous carbon-based composite material comprises the following steps: S1. Preparation of porous carbon materials: S101. The biomass raw material is washed with water and dried, crushed, and sieved to obtain a biomass powder; S102. The biomass powder is placed in a porcelain boat in a tubular furnace, and is subjected to a primary calcination treatment at a temperature of 600-700° C. under a nitrogen atmosphere for 2-3 h to obtain a carbonized powder, which is labeled AC; S103. Weigh 2-3 parts of AC and 2-3 parts of compound activator by mass, mix and grind the two for 30-40 minutes, and dry the resulting mixture at 80-90°C for 10-12 hours; S104. The mixture obtained by step S103 is placed in a porcelain boat in a tube furnace, and subjected to secondary calcination at a temperature of 800-900° C. under a nitrogen atmosphere for 2-3 h; S105. The mixture treated in step S4 is taken out, and after cooling to room temperature, washed with hydrochloric acid for 5-6 minutes, then washed with deionized water until neutral, and finally dried at 100-120° C. to obtain a porous carbon material; S2. Preparation of modified porous carbon-based composite materials: S201. Dissolve 1-2 parts of trimethyl borate and 2-4 parts of tetrabutyl titanate in 10-20 parts of ethanol by mass and stir at room temperature for 20-30min to mix well; S202. Adding aqueous ammonia dropwise to the solution obtained in step S201, controlling the pH value of the solution to 9-11, initiating hydrolysis and polycondensation reactions, and continuing stirring for 1-2 hours to form a transparent sol-like substance; S203. The porous carbon material and the sol-like substance obtained in step S202 are mixed uniformly at a mass ratio of 1:5-1:10, and immersed in vacuum conditions for 2-4 hours to facilitate the sol to better enter the pores of the porous carbon material; S204. After the impregnation is completed, the sol containing the porous carbon material is allowed to stand at room temperature for 12-18 hours, and then dried at 60-80° C. for 12-15 hours; S205. Calcine the sol containing the porous carbon material treated in step S204 to obtain the modified porous carbon-based composite material.

[0008] Preferably, in step S101, the biomass raw material is one or more of wood chips, pine cones, rice straw, and sugarcane bagasse.

[0009] Preferably, in step S103, the composite activator is a mixture of K2CO3 and NH4Cl in a mass ratio of 0.001-1:1-3.

[0010] Preferably, in step S105, the concentration of hydrochloric acid is 1-2 mol / L.

[0011] Preferably, in step S202, the concentration of the ammonia water is 0.5-1 mol / L.

[0012] Preferably, during the reaction process of step S202, the temperature is maintained at 30-40°C.

[0013] Preferably, in step S203, the vacuum condition is a vacuum degree of 0.05-0.1 MPa.

[0014] Preferably, in step S205, the working parameters of the calcination treatment are: calcination temperature 400-600°C, calcination time 2-4h, heating rate 5°C / min, and protective gas N2 flow rate 50-80 sccm.

[0015] A modified porous carbon-based composite material is prepared according to the preparation method.

[0016] A modified porous carbon-based composite material prepared according to the preparation method or application of the modified porous carbon-based composite material in wastewater treatment.

[0017] Compared with the prior art, the present invention has the following beneficial effects: 1. The present invention can prepare a porous carbon material with a rich pore structure by compounding an activator component and applying it to the preparation process of the porous carbon material; 2. The present invention successfully doped boron and titanium dioxide into the pores of the porous carbon material by infiltrating a sol containing a boron precursor and a titanium precursor into the pores of the porous carbon material and calcining the sol, thereby achieving a modification of the porous carbon material, so that the modified porous carbon material has a more complex pore structure, more surface defects and richer functional groups. In addition, the doping of boron and titanium dioxide makes the final material have excellent photocatalytic performance, and through the synergistic effect of adsorption and photocatalysis, the removal effect of pollutants in wastewater is greatly enhanced; 2. The present invention has the advantages of simple process, green environmental protection, low cost, etc. At the same time, the prepared modified porous carbon-based composite material has excellent removal performance for metal ions and organic matter in wastewater, showing obvious economic value in the field of sewage treatment. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 The present invention is a flow chart of the preparation process of the porous carbon material.

[0019] Figure 2 This is a process flow chart for preparing the modified porous carbon-based material described in the present invention.

[0020] Figure 3 This is a SEM image of the intermediate product prepared in Example 1 of the present invention: porous carbon material.

[0021] Figure 4 This is a SEM image of the intermediate product prepared in Comparative Example 2 of the present invention: porous carbon material.

[0022] Figure 5 This is a SEM image of the intermediate product prepared in Comparative Example 3 of the present invention: porous carbon material.

[0023] Figure 6 This is a SEM image of the intermediate product prepared in Comparative Example 4 of the present invention: porous carbon material. DETAILED DESCRIPTION

[0024] The present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, rather than all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0025] See also Figure 1-6 , the present invention provides a technical solution: Example 1 A method for preparing a modified porous carbon-based composite material: S1. Preparation of porous carbon materials: S101. Wash the wood chips with water, dry, crush and sieve to obtain wood powder; S102. 10 g of the sawdust powder was placed in a porcelain boat in a tubular furnace and calcined at 600 ° C under a nitrogen atmosphere for 2 h to obtain a carbonized powder, labeled AC-1. S103. Weigh 2 g AC-1, 0.5 g K2CO3, and 1.5 g NH4Cl, respectively, mix and grind them for 30 min, and dry the resulting mixture at 80 ° C for 10 h; S104. The mixture obtained by step S3 is placed in a porcelain boat in a tube furnace, and subjected to secondary calcination at 800° C. under a nitrogen atmosphere for 2 h; S105. The mixture treated in step S4 is taken out, and after cooling to room temperature, washed with 1 mol / L hydrochloric acid for 5 min, then washed with deionized water until neutral, and finally dried at 100° C. to obtain a porous carbon material; S2. Preparation of modified porous carbon-based composite materials: S201. Dissolve 1 g of trimethyl borate and 2 g of tetrabutyl titanate in 10 ml of ethanol and stir at room temperature for 20 min to mix well; S202. Add 0.5 mol / L ammonia water dropwise to the solution obtained in step S201, control the pH value of the solution to 9, and control the temperature to 30° C. to induce hydrolysis and polycondensation reactions, and continue stirring for 1 h to form a transparent sol-like substance; S203. 2 g of the porous carbon material and 10 g of the sol-like substance obtained in step S202 were mixed evenly, and immersed in a vacuum condition of 0.05 MPa for 2 h to facilitate the sol to better enter the pores of the porous carbon material; S204. After the impregnation is completed, the sol containing the porous carbon material is allowed to stand at room temperature for 12 h, and then dried at 60 ° C for 12 h; S205. The sol containing the porous carbon material treated in step S204 is calcined at a temperature of 400°C, a heating rate of 5°C / min, and a calcination time of 2h. After cooling to room temperature, the modified porous carbon-based composite material is obtained.

[0026] Example 2 A method for preparing a modified porous carbon-based composite material: S1. Preparation of porous carbon materials: S101. Wash the wood chips with water, dry, crush and sieve to obtain wood powder; S102. 10 g of the sawdust powder was placed in a porcelain boat in a tubular furnace and calcined at 600 ° C under a nitrogen atmosphere for 2 h to obtain a carbonized powder, labeled AC-2; S103. Weigh 3 g AC-2, 1 g K2CO3, and 2 g NH4Cl, respectively, mix and grind them for 30 min, and dry the resulting mixture at 90 ° C for 10 h; S104. The mixture obtained by step S3 is placed in a porcelain boat in a tube furnace, and subjected to secondary calcination at 800° C. under a nitrogen atmosphere for 3 h; S105. The mixture treated in step S4 is taken out, and after cooling to room temperature, washed with 2 mol / L hydrochloric acid for 5 min, then washed with deionized water until neutral, and finally dried at 120° C. to obtain a porous carbon material; S2. Preparation of modified porous carbon-based composite materials: S201. Dissolve 2 g of trimethyl borate and 4 g of tetrabutyl titanate in 15 ml of ethanol and stir at room temperature for 30 min to mix well; S202. Add 1 mol / L ammonia water dropwise to the solution obtained in step S201, control the pH value of the solution to 11, and control the temperature to 30° C. to induce hydrolysis and polycondensation reactions, and continue stirring for 2 h to form a transparent sol-like substance; S203. 2 g of the porous carbon material and 15 g of the sol-like substance obtained in step S202 were mixed evenly, and immersed in a vacuum condition of 0.1 MPa for 3 h to facilitate the sol to better enter the pores of the porous carbon material; S204. After the impregnation is completed, the sol containing the porous carbon material is allowed to stand at room temperature for 12 h, and then dried at 60 ° C for 12 h; S205. The sol containing the porous carbon material treated in step S204 is calcined at a temperature of 500°C, a heating rate of 5°C / min, and a calcination time of 3 hours. After cooling to room temperature, the modified porous carbon-based composite material is obtained.

[0027] Example 3 A method for preparing a modified porous carbon-based composite material: S1. Preparation of porous carbon materials: S101. The pine cones were washed with water and dried, crushed, and sieved to obtain pine cone powder; S102. 10 g of the pine cone powder was placed in a porcelain boat in a tubular furnace and calcined at 700 ° C under a nitrogen atmosphere for 2 h to obtain a carbonized powder, labeled AC-3; S103. Weigh 3 g AC-3, 1.5 g K2CO3, and 1.5 g NH4Cl, respectively, mix and grind them for 30 min, and dry the resulting mixture at 90 ° C for 10 h; S104. The mixture obtained by step S3 is placed in a porcelain boat in a tube furnace, and subjected to secondary calcination at 900° C. under a nitrogen atmosphere for 2 h; S105. The mixture treated in step S4 is taken out, and after it cools to room temperature, it is washed with 1.5 mol / L hydrochloric acid for 5 min, then washed with deionized water until neutral, and finally dried at 120° C. to obtain a porous carbon material; S2. Preparation of modified porous carbon-based composite materials: S201. Dissolve 2 g of trimethyl borate and 4 g of tetrabutyl titanate in 20 ml of ethanol and stir at room temperature for 30 min to mix well; S202. Add 1 mol / L ammonia water dropwise to the solution obtained in step S201, control the pH value of the solution to 10, and control the temperature to 30° C. to induce hydrolysis and polycondensation reactions, and continue stirring for 1.5 h to form a transparent sol-like substance; S203. 2 g of the porous carbon material and 10 g of the sol-like substance obtained in step S202 were mixed evenly, and immersed in a vacuum condition of 0.1 MPa for 3 h to facilitate the sol to better enter the pores of the porous carbon material; S204. After the impregnation is completed, the sol containing the porous carbon material is allowed to stand at room temperature for 12 h, and then dried at 60 ° C for 12 h; S205. The sol containing the porous carbon material treated in step S204 is calcined at a temperature of 400°C, a heating rate of 5°C / min, and a calcination time of 3 hours. After cooling to room temperature, the modified porous carbon-based composite material is obtained.

[0028] Comparative Example: Comparative Example 1: There are the following differences between Comparative Example 1 and Example 1. The only difference is that in Comparative Example 1, step S2 originally existing in Example 1 is omitted, thereby omitting the preparation of modified porous carbon-based composite materials. In Comparative Example 1, only porous carbon materials are prepared, and the remaining steps are exactly the same in Comparative Example 1 and Example 1.

[0029] Comparative Example 2: Comparative Example 2 is different from Example 1 in that the only difference is that in Comparative Example 2, the composite activator component in step S103 originally existing in Example 1 is omitted, and the composite activator component is not added in Comparative Example 2. The remaining steps are exactly the same in Comparative Example 2 and Example 1.

[0030] Comparative Example 3: There are the following differences between Comparative Example 3 and Example 1. The only difference is that in Comparative Example 3, the composite activator component in step S103 originally existing in Example 1 is partially omitted, and only NH4Cl is added in Comparative Example 3. The remaining steps in Comparative Example 3 and Example 1 are exactly the same.

[0031] Comparative Example 4: There are the following differences between Comparative Example 4 and Example 1. The only difference is that in Comparative Example 4, the composite activator component in step S103 originally existing in Example 1 is partially omitted, and only K2CO3 is added in Comparative Example 4. The remaining steps in Comparative Example 4 and Example 1 are exactly the same.

[0032] Comparative Example 5: Comparative Example 5 is different from Example 1 in that, in Comparative Example 5, step S201 originally existing in Example 1 is partially omitted, trimethyl borate is not added, and the remaining steps are exactly the same in Comparative Example 5 and Example 1.

[0033] Performance Test: The specific surface area and pore volume of the porous carbon materials (intermediate products) obtained in Examples 1-3 and Comparative Examples 1-5 were tested, and the test results are as follows: Table 1. Comparison of specific surface area and pore volume of porous carbon materials prepared in Examples 1-3 and Comparative Examples 1-5 The SEM images of the porous carbon materials obtained in Example 1, Comparative Example 2, Comparative Example 3 and Comparative Example 4 are as follows: Figure 3-6 As shown in Table 1 and Figure 3 It can be seen that the porous carbon material prepared in step S1 of Example 1 is a honeycomb structure, and in addition to micropores, there are also a large number of mesopores, which can provide more active sites and a larger reaction space; Figure 4 It can be seen that the intermediate porous carbon material prepared in Comparative Example 2 is an irregular solid three-dimensional structure. From Table 1, it can be seen that the specific surface area and pore volume of the porous carbon material obtained in Comparative Example 2 are very small; Figure 5 As shown, Comparative Example 3 is an intermediate product porous carbon material prepared by adding only NH4Cl. Compared with Comparative Example 2, flakes and smooth spheres appear. From Table 1, it can be seen that the specific surface area and pore volume of the porous carbon material obtained are increased, indicating that NH4Cl has a certain activation and pore-forming effect; Figure 6As shown, Comparative Example 4 is a porous carbon material prepared by adding only K2CO3, and the surface appears to be a rough morphology with small particles attached. It can be seen from Table 1 that compared with Example 1, the specific surface area and pore volume of the porous carbon material obtained in Comparative Example 4 are still relatively small, indicating that the activation of carbon by K2CO3 alone is not sufficient, and the formed pore structure is not rich enough; Figure 3-6 Compared with Table 1, the composite activator provided by the present invention has a synergistic effect on the pore formation of biochar, which can greatly increase the pore volume of the prepared porous carbon material, create favorable conditions for the subsequent introduction of boron-containing precursors and titanium precursors, and finally prepare a composite material containing porous carbon, boron species and TiO2.

[0034] The modified porous carbon-based composite materials prepared in Examples 1-3 and Comparative Examples 1-5 were put into simulated wastewater for adsorption experiments. The specific steps are as follows: 500 ml of Cd 2+ , Cu 2+ Cr 3+ , Pb 2+ , and methylene blue concentrations were all 100 mg / L simulated contaminated liquid, the modified porous carbon-based composite materials prepared in Examples 1-3 and Comparative Examples 1-5 were respectively put into the above simulated contaminated liquid, and the dosage was 1% of the simulated contaminated liquid. The adsorption experiments were carried out under the conditions of 300W xenon lamp irradiation and dark protection, the temperature was 25°C, the stirring rate was 800 r / min, the time was 30min, and the sedimentation was filtered to calculate Cd 2 + , Cu 2+ Cr 3+ , Pb 2+ , the removal rate of methylene blue, the results are as follows: Table 2. Summary of adsorption experimental data As can be seen from Table 2, the porous carbon-based composite materials prepared in Examples 1-3 of the present invention all show good removal capabilities for heavy metal ions and organic pollutants, can be used to treat common pollutant components in wastewater, and have good application prospects. Under dark conditions, the modified porous carbon-based composite materials still have significant removal efficiency for a variety of pollutants, indicating that the prepared modified porous carbon-based composite materials have good adsorption effects; the difference in adsorption performance between Example 1 and Comparative Example 1 proves that the present invention successfully dopes boron and titanium dioxide into the pores of the porous carbon material by infiltrating a sol containing a boron precursor and a titanium precursor into the pores of the porous carbon material and calcining the sol, thereby achieving modification of the porous carbon material, so that the modified porous carbon material has a more complex pore structure, more surface defects and richer functional groups, thereby enhancing its adsorption of heavy metal ions and organic matter in wastewater. Energy; The difference in removal rate of different pollutants between Example 1 and Comparative Examples 2-4 under dark and light-proof conditions shows that the present invention can greatly improve the pore volume and the number of mesopores of the porous carbon material and improve its adsorption performance by using a composite activator and applying it to the preparation process of the porous carbon material. Furthermore, the photocatalytic experiment conducted under the irradiation of a 300W xenon lamp shows that a larger pore volume and a larger number of mesopores are conducive to the introduction of more boron-containing precursors and titanium precursors into the pores of the porous carbon material, so that the porous carbon-based composite material obtained after calcination can degrade pollutants through a synergistic photocatalytic reaction, thereby improving the removal efficiency of pollutants in wastewater, which is consistent with the phenomenon described in the aforementioned SEM characterization part; The difference in pollutant removal rate between Example 1 and Comparative Example 5 is presumed to be due to the fact that the boron element was not introduced, which reduced the number of holes on the surface of titanium dioxide and the oxidation sites, thereby reducing its photocatalytic ability.

[0035] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.

Claims

1. A method for preparing a modified porous carbon-based composite material, characterized in that: The following steps are involved: S1. Preparation of porous carbon materials: S101. The biomass raw material is washed with water and dried, crushed, and sieved to obtain a biomass powder; S102. The biomass powder is placed in a porcelain boat in a tubular furnace, and is subjected to a primary calcination treatment at a temperature of 600-700° C. under a nitrogen atmosphere for 2-3 h to obtain a carbonized powder, which is labeled AC; S103. Weigh 2-3 parts of AC and 2-3 parts of compound activator by mass, mix and grind the two for 30-40 minutes, and dry the resulting mixture at 80-90°C for 10-12 hours; S104. The mixture obtained by step S103 is placed in a porcelain boat in a tube furnace, and subjected to secondary calcination at a temperature of 800-900° C. under a nitrogen atmosphere for 2-3 h; S105. The mixture treated in step S4 is taken out, and after cooling to room temperature, washed with hydrochloric acid for 5-6 minutes, then washed with deionized water until neutral, and finally dried at 100-120° C. to obtain a porous carbon material; S2. Preparation of modified porous carbon-based composite materials: S201. Dissolve 1-2 parts of trimethyl borate and 2-4 parts of tetrabutyl titanate in 10-20 parts of ethanol by mass and stir at room temperature for 20-30 min to mix well; S202. Adding aqueous ammonia dropwise to the solution obtained in step S201, controlling the pH value of the solution to 9-11, initiating hydrolysis and polycondensation reactions, and continuing stirring for 1-2 hours to form a transparent sol-like substance; S203. The porous carbon material and the sol-like substance obtained in step S202 are mixed uniformly at a mass ratio of 1:5-1:10, and immersed in vacuum conditions for 2-4 hours to facilitate the sol to better enter the pores of the porous carbon material; S204. After the impregnation is completed, the sol containing the porous carbon material is allowed to stand at room temperature for 12-18 hours, and then dried at 60-80° C. for 12-15 hours; S205. Calcine the sol containing the porous carbon material treated in step S204 to obtain the modified porous carbon-based composite material.

2. The method for preparing a modified porous carbon-based composite material according to claim 1, characterized in that: In step S101, the biomass raw material is one or more of wood chips, pine cones, rice straw, and sugarcane bagasse.

3. The method for preparing a modified porous carbon-based composite material according to claim 1, characterized in that: In step S103, the composite activator is a mixture of K2CO3 and NH4Cl in a mass ratio of 0.001-1:1-3.

4. The method for preparing a modified porous carbon-based composite material according to claim 1, characterized in that: In step S105, the concentration of hydrochloric acid is 1-2 mol / L.

5. The method for preparing a modified porous carbon-based composite material according to claim 1, characterized in that: In step S202, the concentration of the ammonia water is 0.5-1 mol / L.

6. The method for preparing a modified porous carbon-based composite material according to claim 5, characterized in that: During the reaction of step S202, the temperature is maintained at 30-40°C.

7. The method for preparing a modified porous carbon-based composite material according to claim 1, characterized in that: In step S203, the vacuum condition is a vacuum degree of 0.05-0.1 MPa.

8. The method for preparing a modified porous carbon-based composite material according to claim 1, characterized in that: In step S205, the working parameters of the calcination treatment are: calcination temperature 400-600°C, calcination time 2-4h, heating rate 5°C / min, and protective gas N2 flow rate 50-80 sccm.

9. A modified porous carbon-based composite material, characterized in that: Prepared according to the preparation method according to any one of claims 1 to 8.

10. Use of the modified porous carbon-based composite material obtained by the preparation method according to any one of claims 1 to 8 or the modified porous carbon-based composite material according to claim 9 in wastewater treatment.

Citation Information

Patent Citations

  • Safe and green composite material with functions of absorbing and desorbing formaldehyde, and preparation method of composite material

    CN107213868A

  • Preparation method of interstitial boron doping titanium dioxide photocatalytic material and application

    CN108452788A

  • Porous carbon material with high specific surface area and high yield as well as auxiliary activation preparation method and application thereof

    CN113213474A

  • Integrally-formed nitrogen-containing blocky porous carbon material as well as preparation method and application thereof

    CN114053996A

  • Preparation method and application of biomass-derived graded porous biochar adsorbent

    CN115025760A